Efficacy of Pneumococcal Vaccine 13-Valent (PCV13) for Pneumonia Prevention - Uaesuwanna, Natcha; Yingratsuk, Konlayut; Masugarut, Pisitchai; Tangsucharit, Pattaraphon; Ariyapim, Naowakun; Rittirod, Theera (Srinagarind Medical Journal, 2024)
The purpose of this article was to study the Pneumococcal vaccine 13-valent (PCV13) for the prevention of pneumonia, providing a source of knowledge for those interested in PCV13. From 2023 to 2024, the authors rigorously reviewed research papers from both Thailand and international sources, including reputable organizations such as the World Health Organization, the Centers for Disease Control of the United States, the National Center for Biotechnology Information of the United States, and a vaccine textbook from the Bureau of General Communicable Diseases, Department of Disease Control, Thailand. A total of 34 articles were scrutinized to ensure the reliability of the information. The findings indicate that PCV13 is safe for preventing pneumonia, reduces the severity of the disease, and can lower the mortality rate without causing any serious side effects that could lead to death.